Evaluasi Pelatihan Kepemimpinan Administrator dalam Implementasi Program Pengembangan Kepegawaian di Pusat Pengembangan Kepegawaian ASN Badan Kepegawaian Negara - Deffryan Octiorizaldy; Masduki Ahmad; Siti Rochanah (Syntax Corporation Indonesia, 2024)
This study aims to find out the results of the Evaluation of Leadership Training of Administrators in the Implementation of Competence Development Programmes at the ASN Competency Development Centre of the State Competition Agency using the CIPP evaluation model. (Context, Input, Process, Product). The evaluation results consist of 4 CIPP components, showing that: 1) On the Context component, Peg ASN BKN has a basis in the maintenance of the PKA program, the purpose of the maintenance is in accordance with the maintenance guidelines, as well as the analysis of the needs of the program in conformity with the Maintenance Guidelines; 2) On the Input component Peg Asn BKN have a good SDM, according to the LAN standard, have the budgeting documentation and curriculum that conforms to the maintenance directives, and complete prasarana means; 3) On the Process component from the planning process until the evaluation process is carried out with policy measures; 4) On the Product component in view of the assessment results, the goal of PKA programme maintenance has been achieved. Other findings were obtained, namely: 1) There are more tasks where to get caught into the organizing committee and widyaiswara; 2) Additional learning studio facilities; 3) Socialization through social media and online registration. As for the recommendation to the organizer, in forming a team in a training maintenance to give his task is not excessive or two responsibilities, thus will improve efficiency and efficiency in a job.